Urban Space and Gender in the Work of Hildegard Rosenthal and Sonia Madrigal - Salles, Cecilia; Negrão, Wilson Renato (Farol, 2026)
This study analyzes the creative processes of Hildegard Rosenthal and Sonia Madrigal to discuss the relationships between gender, photography, and urban space. Drawing on process criticism, it identifies common procedures that highlight the construction of visual narratives in which women inhabit the city as protagonists, reaffirming their autonomy in the production and representation of their own images.